2002
DOI: 10.1099/00221287-148-7-2203
|View full text |Cite
|
Sign up to set email alerts
|

Glycine binds the transcriptional accessory protein GcvR to disrupt a GcvA/GcvR interaction and allow GcvA-mediated activation of the Escherichia coli gcvTHP operon

Abstract: The Escherichia coli gcvTHP operon is under control of the LysR-type transcriptional regulator GcvA. GcvA activates the operon in the presence of glycine and represses the operon in its absence. Repression by GcvA is dependent on a second regulatory protein, GcvR. Generally, LysR-type transcriptional regulators bind to specific small co-effector molecules which results in either their altered affinity for specific binding sites on the DNA or altered ability to bend the DNA, resulting in either activation or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Again, this is an unusual situation because in most instances LysR-type regulated systems are very simple and involve a single regulatory component, the activator, which is able to directly sense the effector and to regulate transcription. In some systems, an additional regulatory protein has been shown to modulate the activity of the activator by binding to it and thus preventing its function (23). However, to our knowledge, this is the first report of a LysR-type activator that requires an auxiliary protein to activate transcription.…”
Section: Discussionmentioning
confidence: 76%
“…Again, this is an unusual situation because in most instances LysR-type regulated systems are very simple and involve a single regulatory component, the activator, which is able to directly sense the effector and to regulate transcription. In some systems, an additional regulatory protein has been shown to modulate the activity of the activator by binding to it and thus preventing its function (23). However, to our knowledge, this is the first report of a LysR-type activator that requires an auxiliary protein to activate transcription.…”
Section: Discussionmentioning
confidence: 76%
“…GcvB is activated by the glycine cleavage system regulator, GcvA, under glycine-rich conditions (40). This interaction is dependent upon Lrp binding and is negatively regulated by GcvR when glycine is limiting (41). Using quantitative PCR, we measured relative expression levels of gcvB in wild-type, ΔgcvA, and Δlrp, with and without glycine addition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that T. vaginalis has two H proteins, encoded by independent genes, both of which are effective substrates of the L protein ( Table 1). The H proteins in plants (2), mammals (6), Escherichia coli (19), and yeast (33) are encoded by a single gene. In some plants, tissue-specific alternative splicing results in two H proteins with or without an N-terminal extension of two amino acids (23,24).…”
Section: Discussionmentioning
confidence: 99%